THE ANXIETY OF WESLEY GIBSON IN MICHAEL BRANDT'S WANTED MOVIE (2008): A PSYCHOANALYTICAL APPROACH - PUJIYANTO, EKO (2010)
The major problem of this study is how anxiety reflected on the major character personality. The objectives of this study are to analyze the movie based on the structural element and to analyze anxiety on Michael Brandt's Wanted movie based on psychoanalytic approach. This study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is Wanted movie, a movie by Michael Brandt. The data sources are primary and secondary data sources. The primary data sources is the movie itself, Wanted movie, and the secondary data sources are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive qualitative analysis. The result of the study is as follows. Firstly, based on structural analysis, Wanted movie has a good quality in all parts of the movie that tells one's search for self identity resulting in great anxieties. The characters, theme, setting, point of view, plot, casting, mise-en-scene, cinematography, editing and sound influence each other. One of the major characters of Wanted movie is Wesley Gibson as a cryptology who tries to know about his family. Related to the story of the movie, Timur Bekmambetov does his jobs well as the director of this movie. Secondly, based on psychoanalytic analysis of this movie is the problem of Wesley Gibson which makes he anxiety to face his life. Wesley Gibson's personality makes great anxieties because he wants to know about himself and his family. He is a man who is separated from his father when he was in seven day old; he lived with his girlfriend and work as an account manager